Russula orientalovirescens sp. nov., a common Southeast Asian edible fungus is different from the European look-alike R. virescens. - Komsit Wisitrassameewong; Slavomír Adamčík; Katarína Adamčíková; Song-Ming Tang; Narumon Tangthirasunun; Boontiya Chuankid; Olivier Raspé (PLoS ONE)
Green-cracking Russulas are edible fungi that are widely consumed and traded in Southeast Asia. Asian collections of this morphotype were frequently identified as R. virescens in local literature. Multilocus phylogenetic analyses of ITS nrDNA, rpb2 and tef1 regions presented in this study strongly supported that the majority of green cracking Russula collections from Southeast Asia represent a species different from European R. virescens and these collections are described here as R. orientalovirescens sp. nova. Analysis of ITS barcoding region confirmed that published sequence data from China, Laos and Myanmar reported this species as R. virescens. In addition, this analysis showed that the species is widely distributed in Southeast Asia from Malayan Peninsula to Japan, preferring areas with dry season, and is associated with coniferous and deciduous trees as well as heterotrophic plants. Morphological analyses and detailed comparison with recent collections of R. virescens showed that R. orientalovirescens differs from the latter by larger spores and shorter and more abundant pileocystidia. Green-cracking Russula species with distinctly areolate pileus formed a monophyletic lineage where our new species is grouped with Asian R. viridirubrolimbata, European R. virescens and North American R. parvovirescens. Few publicly available ITS sequences from Southeast Asia clustered with either European or North American species suggesting that the phylogenetic lineage of green-cracking Russulas urgently require further attention.